Equality, Responsibility, and Culture: A Comment on Alan Patten’s Equal Recognition - Quong, Jonathan (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2015)
Alan Patten presents his account of minority rights as broadly continuous with Ronald Dworkin’s theory of equality of resources. This paper challenges this claim. I argue that, contra Patten, Dworkin’s theory does not provide a basis to offer accommodations or minority rights, as a matter of justice, to some citizens who find themselves at a relative disadvantage in pursuing their plans of life after voluntarily changing their cultural or religious commitments.